Within-shoal phenotypic homogeneity affects shoaling preference in a killifish. (8th August 2018) - Cattelan, Silvia; Griggio, Matteo
Abstract : Anti-predator benefits associated with living in groups are multiple and taxonomically widespread. In fish shoals, individuals can exploit the confusion effect, whereby predators struggle to target a single individual among several individuals. Theory predicts that the confusion effect could be aided by homogeneity in appearance; thus, individuals should group by phenotypic characteristics, contributing to generating high within-shoal phenotypic homogeneity. While assortments by body size have been extensively documented, almost nothing is known about whether within-shoal homogeneity in body pigmentation affects shoaling preference. To investigate this issue, we used the Mediterranean killifish, Aphanius fasciatus, a shoaling species characterized by conspicuous vertical bars on body sides. Individual females were given a choice between two novel shoals characterized by either a high or low degree of homogeneity in the number of bars. As predicted, individual females preferentially associated with the shoal showing the higher phenotypic homogeneity. Our data demonstrated that fish might associate with the shoal that maximizes phenotypic homogeneity in body pigmentation, irrespective of their own phenotype.